The Emergence of AI in Educational Settings: The Transformative Influence of Artificial Intelligence on Learning Process - Rachmi Rachmi (Education Studies and Teaching Journal (EDUTECH), 2024)
The integration of Artificial Intelligence (AI) in education has been a significant research focus from 2019 to 2024. This research aims to comprehensively investigate the effectiveness of AI interventions in education, taking into account various contexts and influencing factors. The research method used is systematic literature, with research results showing that AI interventions have great potential in improving learning outcomes, 21st century skills, motivation, student engagement, and reducing educational gaps. The implications of this research are important for practitioners, researchers, and policy makers in their efforts to advance adaptive and inclusive education in the era of artificial intelligence.